Use of innovative technologies in group-based reminiscence interventions in older adults’ with dementia: a scoping review - Gil, Isabel (2020)
Background: Reminiscence therapy (RT) emerges in the literature as a non-pharmacological intervention commonly implemented in groups of older adults with dementia, and which has significant positive results in outcomes such as cognition and depressive symptomatology. Simultaneously, we witness the gradual addition of innovative technologies in non-pharmacological interventions in this population segment. However, no studies have synthesized the main contributions of the use of technology in group-based RT sessions. Aim: To map the available evidence on group-based RT sessions/activities aided by technological innovations, and critically discussed the potentialities and weaknesses of its use. Methods: Scoping review following the Joanna Briggs Institute methodology. Two independent reviewers analyzed the relevance of the studies, extracted and synthesized data. Results: Seven studies were included. Overall, the use of technological aids potentiates the interaction and communication between older adults with dementia, staff, and relatives. Nevertheless, issues related to ergonomics, connectivity, and intention of use emerge as recurrent pitfalls. Conclusion: While technological aids can foster a more personalized and dynamic group-based RT session, the development of such innovations must follow an user-centered approach that involves older adults with different stages of dementia in order to create solutions with significance and applicability to its end-users.